Successful use of tapering strips for hyperbolic reduction of antidepressant dose: a cohort study. (August 2021) - Groot, Peter C.; van Os, Jim
Background: Tapering strips facilitate antidepressant discontinuation, allowing for personalised titration of discontinuation to the intensity of withdrawal. A tapering strip consists of antidepressant or other medication, packaged in a 28-day roll of daily pouches, each with the same or slightly lower dose than the one before. Previous studies demonstrated 70% real-world effectiveness of tapering strips. Here, we present a third, questionnaire-based retrospective cohort study in a large sample. Methods: Patients whose doctor had prescribed tapering strips between October 2015 and December 2018 were sent a questionnaire for participation after completion of tapering between December 2015 and January 2020. Of 1240 individuals who returned a questionnaire (response rate: 59%), 987 (80%) used an antidepressant, of whom 824 (83%) had wished to discontinue their antidepressant. Results: The sample was demographically representative of antidepressant users in the Netherlands. Less than 40% of participants had heard of tapering strips through their clinicians – Internet was the most frequent source. Of the 824 individuals, 341 (41%) had used strips for tapering venlafaxine, 206 (25%) for paroxetine and 277 (34%) for other antidepressants. Median duration of antidepressant use was 5–10 years, and most (71%) had tried to come off without tapering strips at least once. Most patients (72%) were able to discontinue their antidepressant, using a median of two strips to taper over a median period of 56 days. Females and individuals with (1) more severe experience of withdrawal during the use of tapering strips, (2) more years of use of antidepressant medication and (3) more previous attempts at discontinuation were less likely to be able to discontinue their antidepressant medication with tapering strips. Conclusion: The results of this study validate, for the third time, the observation that tapering strips can address the problem of antidepressant withdrawal symptoms in individuals attempting to discontinue antidepressants.